2006
DOI: 10.1104/pp.106.080697
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ntf4, a Tobacco Mitogen-Activated Protein Kinase, during Plant Defense Response and Its Involvement in Hypersensitive Response-Like Cell Death

Abstract: Mitogen-activated protein kinase (MAPK) cascades are important signaling modules in eukaryotic cells. They function downstream of sensors/receptors and regulate cellular responses to external and endogenous stimuli. Recent studies demonstrated that SIPK and WIPK, two tobacco (Nicotiana spp.) MAPKs, are involved in signaling plant defense responses to various pathogens. Ntf4, another tobacco MAPK that shares 93.6% and 72.3% identity with SIPK and WIPK, respectively, was reported to be developmentally regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 76 publications
6
82
0
3
Order By: Relevance
“…The authors also concluded that some of the published loss-of-function studies that targeted SIPK (41,42) most likely also silenced Ntf4, and that systematic loss-offunction studies of each of the two MAPK paralogs are lacking. They further suggested that the presence of two highly homologous MAPKs in certain solanaceous plants may be adaptive, either because the two MAPKs do have some different yetunknown functions or because of a gene-dosage effect (40). Our results are consistent with the latter scenario.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The authors also concluded that some of the published loss-of-function studies that targeted SIPK (41,42) most likely also silenced Ntf4, and that systematic loss-offunction studies of each of the two MAPK paralogs are lacking. They further suggested that the presence of two highly homologous MAPKs in certain solanaceous plants may be adaptive, either because the two MAPKs do have some different yetunknown functions or because of a gene-dosage effect (40). Our results are consistent with the latter scenario.…”
Section: Discussionsupporting
confidence: 82%
“…The tobacco genome also contains two highly homologous MAPKs of the A2 subgroup, SIPK and Ntf4. Recently, it was shown that their functions are largely redundant (40). The authors also concluded that some of the published loss-of-function studies that targeted SIPK (41,42) most likely also silenced Ntf4, and that systematic loss-offunction studies of each of the two MAPK paralogs are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Naf4 is a close homolog of SIPK, which might be derived from a recent gene duplication event (Ren et al, 2006;Wu et al, 2007a). Remarkably, qRT-PCR showed that even when UT and AZ plants were not induced (Fig.…”
Section: Mapk Genes Have Different Transcript Levels In Ut and Az Plantsmentioning
confidence: 97%
“…Naf4 shows high sequence homology to SIPK and thus may have a similar function (Ren et al, 2006). MPK4 is known to be involved in pathogen resistance and woundinduced responses but has as yet no known function in herbivore resistance (Petersen et al, 2000;Gomi et al, 2005).…”
Section: Natural Variation In Herbivore-induced Signaling Eventsmentioning
confidence: 99%
“…In tobacco (Nicotiana tabacum), wound-induced protein kinase (WIPK) and salicylic acid-induced protein kinase (SIPK) are pathogen-responsive MAPKs (Seo et al, 1995;Zhang and Klessig, 1997). MEK2, a tobacco MAPK kinase, functions upstream of SIPK and WIPK (Ren et al, 2006). The MEK2-SIPK/WIPK cascade (MEK2 cascade) is highly conserved in diverse plant species and participates in defense responses (Tanaka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%